1982
DOI: 10.1113/expphysiol.1982.sp002658
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Urine Osmolality in Fetal Sheep

Abstract: SUMMARYUrine osmolality was measured daily from day of cannulation (80-110 d) until term in six chronically cannulated ovine fetuses. Fetal urine was hypertonic to plasma following surgery, and 24-36 h before parturition. On fifty-five occasions plasma antidiuretic hormone (ADH) concentration was measured concurrently with urine osmolality. When fetal urine osmolality was 154 + 45 mosmol/kg water, plasma ADH was 5 6 + 2 1 pg/ml (mean + S.D.; n = 33) in fetuses less than 120 d gestation. In ten samples from fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The absence of an increase in GFR, with cortisol infusion, in the mature fetuses, in addition to a more effective distal tubular sodium reabsorption, may be responsible for the absence of a natriuretic response in the mature animal. The decrease in urine osmolality that occurs as fetuses mature also argues that distal mechanisms are more effective in NaCl reabsorption before term (32).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of an increase in GFR, with cortisol infusion, in the mature fetuses, in addition to a more effective distal tubular sodium reabsorption, may be responsible for the absence of a natriuretic response in the mature animal. The decrease in urine osmolality that occurs as fetuses mature also argues that distal mechanisms are more effective in NaCl reabsorption before term (32).…”
Section: Resultsmentioning
confidence: 99%
“…The two groups of animals studied were divided at 120 d gestation because there is evidence that fetuses younger than 120 d behave differently from fetuses older than 120 d both in their capacity to release ADH (Robillard et al 1981;Rose et al 1981) and the sensitivity of the fetal kidney to infused ADH (Wintour et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested previously that the renal function of the premature or growth-retarded neonate might resemble that of the fetus rather than that of the normal newborn, and shown that cortisol has a unique natriuretic effect in the immature ovine fetal kidney (5). The immature fetal kidney is less responsive to endogenous or exogenous AVP than is the kidney of the nearterm fetus (6,7). With the discovery of an endogenous natriuretic peptide of atrial origin (8,9) it seemed to be important to find out whether this peptide exerted any influence over sodium handling by the immature fetal kidney.…”
mentioning
confidence: 99%